2003
DOI: 10.1002/gepi.10218
|View full text |Cite
|
Sign up to set email alerts
|

Power of multifactor dimensionality reduction for detecting gene‐gene interactions in the presence of genotyping error, missing data, phenocopy, and genetic heterogeneity

Abstract: The identification and characterization of genes that influence the risk of common, complex multifactorial diseases, primarily through interactions with other genes and other environmental factors, remains a statistical and computational challenge in genetic epidemiology. This challenge is partly due to the limitations of parametric statistical methods for detecting genetic effects that are dependent solely or partially on interactions with other genes and environmental exposures. We previously introduced mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
463
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 517 publications
(469 citation statements)
references
References 18 publications
5
463
0
1
Order By: Relevance
“…The first four models, Ep1-Ep4, modified from the models used by Becker et al [2005], are two-locus epistatic models that exhibit interaction effects as well as main effects (marginal effects). The last four models, P1-P4 as described by Ritchie et al [2003] and Sha et al [2006], are four pure interaction models that exhibit interaction effects in the absence of any main effects when the Hardy-Weinberg equilibrium is assumed.…”
Section: Simulation Studies For Evaluating Powermentioning
confidence: 99%
See 2 more Smart Citations
“…The first four models, Ep1-Ep4, modified from the models used by Becker et al [2005], are two-locus epistatic models that exhibit interaction effects as well as main effects (marginal effects). The last four models, P1-P4 as described by Ritchie et al [2003] and Sha et al [2006], are four pure interaction models that exhibit interaction effects in the absence of any main effects when the Hardy-Weinberg equilibrium is assumed.…”
Section: Simulation Studies For Evaluating Powermentioning
confidence: 99%
“…Forming haplotypes over multiple neighboring loci in one gene can increase the power of gene mapping studies [Zhao et al, 2000;Fallin et al, 2001;Schaid et al, 2002;Zhang et al, 2003], but these methods only work locally in a given genomic region. Although various authors have postulated the need for methods that investigate multiple interacting genes jointly [Tiwari and Elston, 1998;Cox et al, 1999;Templeton, 2000;Wilson, 2001;Cordell et al, 2001;Cordell, 2002;Culverhouse et al, 2002;Moore and Williams, 2002;Moore, 2003], only a few viable approaches in this direction exist [Hoh et al, 2001;Xiong et al, 2002;Potter, 2006;Dudbridge et al, 2006;Ritchie et al, 2001Ritchie et al, , 2003Moore, 2004;Nelson et al, 2001;Culverhouse et al, 2004;Sha et al, 2006;Millstein et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multifactor dimensionality reduction (MDR) is a model-free, non-parametric data reduction method for detecting multilocus genotype combinations that predict disease risk for common, complex disease. Empirical studies with simulated data indicate that MDR has good power to identify high-order gene-gene interactions, 17 and has been proven to be maximally efficient at discriminating between clinical end points using multilocus genotype data. 18 Studies with simulated data (with multiple models of different allele frequencies and heritability) have also shown that MDR has high power to identify interactions in the presence of many types of noise commonly found in real data sets -including missing data and genotyping error.…”
Section: Introductionmentioning
confidence: 99%
“…18 Studies with simulated data (with multiple models of different allele frequencies and heritability) have also shown that MDR has high power to identify interactions in the presence of many types of noise commonly found in real data sets -including missing data and genotyping error. 17 Additionally, MDR has been shown to have better power to detect interactions than classification and regression trees and stepwise logistic regression (unpublished results).…”
Section: Introductionmentioning
confidence: 99%